Mandibular ramus shape of Australopithecus sediba suggests a single variable species. Issue 100 (November 2016) - Ritzman, Terrence B.; Terhune, Claire E.; Gunz, Philipp; Robinson, Chris A.
Abstract: The fossils from Malapa cave, South Africa, attributed to Australopithecus sediba, include two partial skeletons—MH1, a subadult, and MH2, an adult. Previous research noted differences in the mandibular rami of these individuals. This study tests three hypotheses that could explain these differences. The first two state that the differences are due to ontogenetic variation and sexual dimorphism, respectively. The third hypothesis, which is relevant to arguments suggesting that MH1 belongs in the genus Australopithecus and MH2 in Homo, is that the differences are due to the two individuals representing more than one taxon. To test these hypotheses, we digitized two-dimensional sliding semilandmarks in samples of Gorilla, Pan, Pongo, and Homo, as well as MH1 and MH2. We document large amounts of shape variation within all extant species, which is related neither to ontogeny nor sexual dimorphism. Extant species nevertheless form clusters in shape space, albeit with some overlap. The shape differences in extant taxa between individuals in the relevant age categories are minimal, indicating that it is unlikely that ontogeny explains the differences between MH1 and MH2. Similarly, the pattern of differences between MH1 and MH2 is inconsistent with those found between males and females in the extant sample, suggesting that it is unlikely that sexual dimorphism explains these differences. While the difference between MH1 and MH2 is large relative to within-species comparisons, it does not generally fall outside of the confidence intervals for extant intraspecific variation. However, the MH1-MH2 distance also does not plot outside and below the between-species confidence intervals. Based on these results, as well as the contextual and depositional evidence, we conclude that MH1 and MH2 represent a single species and that the relatively large degree of variation in this species is due to neither ontogeny nor sexual dimorphism.